1997
DOI: 10.1136/jnnp.63.4.434
|View full text |Cite
|
Sign up to set email alerts
|

Hallucinosis in idiopathic Parkinson's disease

Abstract: Background-Hallucinosis is a complication of the treatment of idiopathic Parkinson's disease commonly thought to aZict older, chronically medicated, cognitively impaired patients. However, patients with idiopathic Parkinson's disease of short durationexperiencinghallucinosisonrelatively low doses of dopaminergic medication have been found. The aim, therefore, was to investigate the homogeneity of a population of patients with idiopathic Parkinson's disease and hallucinosis. Methods-The clinical, demographic, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
121
3
12

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(149 citation statements)
references
References 19 publications
13
121
3
12
Order By: Relevance
“…Die Prävalenz psychotischer Symptome bei Parkinson-Patienten lag vor Einführung der dopaminergen Therapie bei 5-10 % [5] und wird heute mit 15-40 % [6][7][8][9][10][11][12][13][14][15] angegeben. Fénelon und Mitarbeiter untersuchten 216 ambulante Parkinson-Patienten mit einer mittleren Krankheitsdauer von 9 Jahren und fanden für Halluzinationen eine Präva-lenz von 40 % innerhalb der letzten drei Monate und eine Lebenszeitprävalenz von 46 % [12].…”
Section: Prävalenzunclassified
See 1 more Smart Citation
“…Die Prävalenz psychotischer Symptome bei Parkinson-Patienten lag vor Einführung der dopaminergen Therapie bei 5-10 % [5] und wird heute mit 15-40 % [6][7][8][9][10][11][12][13][14][15] angegeben. Fénelon und Mitarbeiter untersuchten 216 ambulante Parkinson-Patienten mit einer mittleren Krankheitsdauer von 9 Jahren und fanden für Halluzinationen eine Präva-lenz von 40 % innerhalb der letzten drei Monate und eine Lebenszeitprävalenz von 46 % [12].…”
Section: Prävalenzunclassified
“…illusionären Verkennungen mit völlig erhaltener Einsicht bis zu schwersten paranoiden Psychosen, die wegen der dabei häufig erforderlichen starken Reduktion der Parkinson-Medikation zu einer bedrohlichen Verschlechterung der motorischen Parkinson-Symptomatik führen können. Visuelle Halluzinationen stellen die häufigste psychotische Störung bei Parkinson-Patienten dar [7,9,12]. Geformte visuelle Halluzinationen bestehen in einfachen oder detailreichen, häufig farbintensiven Bildern von Menschen oder Tieren, seltener von Objekten.…”
Section: Klinische Präsentationunclassified
“…Hallucinations are common symptoms in these patients. Visual hallucinations are a well recognized problem in patients with Parkinson's disease (3)(4)(5)(6), whereas auditory hallucinations are less common (7)(8)(9). As a result, information about the mechanism of auditory hallucinations in Parkinson's disease is not generally available.…”
Section: Introductionmentioning
confidence: 99%
“…Graham et al [2], reported that 70% of their patients with hallucinations had retained insight. This seems a contradiction because psychosis is a mental disorder characterized by symptoms, such as delusions or hallucinations that indicate an impaired contact with reality [3].…”
mentioning
confidence: 99%